ANALISIS PENGARUH PELATIHAN PROGRAM SEKOLAH PENGGERAK TERHADAP HASIL PELATIHAN (STUDI KASUS: PRE DAN POST TEST PROVINSI JAWA BARAT) - Revyanza, Avinda Rizky; Sofiyat, Ali Ilham; Saputra, Andri (Fakultas Sains Dan Teknologi, 2025)
This study employed non-parametric analysis using the Wilcoxon Signed Rank test and Spearman correlation test. This study aimed to analyze the effect of the School Mover Program training on training outcomes in West Java Province, focusing on the evaluation of pre-test and post-test results. The population used was 619 respondents in West Java Province, with a sample size of 119 respondents. Data were collected by the Ministry of Education, Culture, Research, and Technology through a 21-question questionnaire and processed using SPSS version 25 software. The results showed that the pre-test and post-test data were not normally distributed, with a significance value (Sig.) of 0.000 for each. The Wilcoxon Signed Rank test indicated a significant difference between pre-test and post-test scores, with 104 of the 119 respondents experiencing an increase in their scores after the training. Furthermore, a Spearman correlation analysis showed a weak relationship between pre-test and post-test scores, with a correlation coefficient of 0.247 and a 2-tailed significance value of 0.011. The results of this study concluded that the School Mover Program training was effective in improving participant competency. This research is expected to provide useful information for improving the effectiveness of future training programs.